Social movements in crisis: locating disaster communities in rhetoric and rhetoric in disaster communities - Archer, Max (Kansas State University, 2008)
Modern disasters have shown a disturbing tendency to disrupt normal community life by severing the connection between social services and the populace. Emergency managers realize that responding to disasters presents many unique communication challenges, both on the technical level and the symbolic level. Communities have begun to organize themselves to prepare for and respond to disasters in the event that emergency response agencies confront such challenges. The Community Emergency Response Team (CERT) program was established to train and deploy citizens to supplement the efforts of first responders. The CERT program's website provides information about the program, how to form a CERT and other training and administrative information. A close textual reading of the CERT website enables the rhetorical critic to identify the use of fantasy themes that construct a vision that defines CERT as a rhetorical community. Upon identifying the rhetorical vision at work, a comparison can be made to the features that define a social movement. Applying social movement theory to citizen initiatives opens the possibility for improving community response and the study of communication issues in disaster response.
Keywords: Rhetoric; Disasters; Communication; Emergency Management; Fantasy Theme Analysis; Mass Communications (0708); Political Science, Public Administration (0617); Speech Communication (0459)